2017
DOI: 10.1016/j.psychres.2017.01.102
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and co-occurrence of hallucinations by modality in schizophrenia-spectrum disorders

Abstract: It is not only unclear why hallucinations in schizophrenia occur with different prevalence by modality, but also to what extent they do. Reliable prevalence estimates of hallucinations by modality in schizophrenia are currently lacking, particularly for non-auditory hallucinations. Studies have also tended to report lifetime, not point prevalence by modality. This study assessed the prevalence and co-occurrence of hallucinations, for both lifetime and point prevalence, across the auditory, visual, olfactory, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 49 publications
5
102
1
1
Order By: Relevance
“…The multimodality of hallucinations is under-documented and under-researched, with <2% of studies included in this review probing hallucinations beyond audition or vision 64 . However, 30-50% of schizophrenia or PD patients report hallucinations in more than one modality 2,112 : olfactory hallucinations are present in 10-13.7% 51,113 and tactile sensations frequently co-occur with auditory hallucinations 1 . Despite the dimensionality of hallucinations, many questionnaires and theoretical models target unimodal accounts.…”
Section: Discussionmentioning
confidence: 99%
“…The multimodality of hallucinations is under-documented and under-researched, with <2% of studies included in this review probing hallucinations beyond audition or vision 64 . However, 30-50% of schizophrenia or PD patients report hallucinations in more than one modality 2,112 : olfactory hallucinations are present in 10-13.7% 51,113 and tactile sensations frequently co-occur with auditory hallucinations 1 . Despite the dimensionality of hallucinations, many questionnaires and theoretical models target unimodal accounts.…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinations are defined as aberrant perceptions in the absence of causative stimuli. These experiences, especially auditory hallucinations, constitute fundamental features of psychosis (64%–80% lifetime prevalence among schizophrenia‐diagnosed patients) and can lead to functional disability and a low quality of life (McCarthy‐Jones et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This quantitative evidence from structural and functional brain scans confirms the long‐standing clinical emphasis on auditory hallucinations as a hallmark symptom of schizophrenia patients. Hearing malevolent voices and other auditory misperceptions (Lim, Hoek, Deen, & Blom, ; Llorca et al, ; McCarthy‐Jones et al, ) might be mediated by impaired preattentive filtering mechanisms (Javitt, ; Javitt & Freedman, ; Javitt & Sweet, ; Rissling & Light, ). Additionally, neuroimaging studies have consistently shown abnormalities of auditory brain regions in schizophrenia using meta‐analyses: (a) structural neuroimaging studies found reduced volume in parts of the auditory cortex in the superior temporal gyrus (Honea, Crow, Passingham, & Mackay, ; Modinos et al, ) and (b) functional investigations have reported increased neural activity in areas related to speech perception, language, and memory during active sensations of speech hallucinations (Allen et al, ; Jardri, Pouchet, Pins, & Thomas, ).…”
Section: Discussionmentioning
confidence: 99%
“…This contention of a key role of binding bodily information is further supported by the first rank of the sense of tasting (gustation). Indeed, misperceptions of imagined tactile or bodily cues (e.g., feeling of insects on the skin) are an often‐encountered clinical symptom in schizophrenia patients (McCarthy‐Jones et al, ; Thomas et al, ). More broadly, this major psychiatric disease is often considered to be a disorder of the self and subjective experience (Fletcher & Frith, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation